Aktivitas Antioksidan Naringenin Dalam Kokristal Naringenin-Asam Fumarat pada Rasio 1:1 dan 1:3 - Amalia Salma Muslimah (Fakultas Farmasi, 2026)
Naringenin is a flavonoid compound that exhibits pharmacological activity, particularly as an antioxidant. However, its application is limited by its low aqueous solubility. One approach to improve the solubility of naringenin is through cocrystal formation with a suitable coformer, such as fumaric acid. This study aimed to evaluate the antioxidant activity of naringenin–fumaric acid cocrystals at molar ratios of 1:1 and 1:3 in comparison with pure naringenin. Cocrystals were prepared using the solvent evaporation method with ethanol p.a. as the solvent. Characterization was conducted using Powder X-Ray Diffraction (PXRD), Differential Scanning Calorimetry (DSC), Fourier Transform Infrared Spectroscopy (FTIR), and Scanning Electron Microscopy (SEM). Antioxidant activity was evaluated using the DPPH method and expressed as IC₅₀ values, followed by statistical analysis using one-way ANOVA. The characterization results confirmed the successful formation of naringenin–fumaric acid cocrystals at both 1:1 and 1:3 ratios. This was evidenced by the appearance of new diffraction peaks in PXRD patterns, the presence of new endothermic peaks in DSC thermograms, shifts in the O–H and C=O functional group wavenumbers in FTIR spectra, and distinct changes in crystal morphology observed by SEM analysis. The antioxidant activity assay showed that pure naringenin exhibited an IC₅₀ value of 3.55 ± 0.044 mg/mL, whereas the cocrystals at ratios of 1:1 and 1:3 exhibited IC₅₀ values of 3.11 ± 0.057 mg/mL and 3.27 ± 0.020 mg/mL, respectively. Statistical analysis demonstrated a significant difference between pure naringenin and both cocrystal forms (p < 0.05). Based on these findings, it can be concluded that the formation of naringenin–fumaric acid cocrystals enhances antioxidant activity compared to pure naringenin. This improvement is associated with changes in crystal packing resulting from noncovalent interactions within the cocrystal system, which reduce lattice energy and increase naringenin solubility. Furthermore, the cocrystal with a 1:1 molar ratio exhibited higher antioxidant activity than the 1:3 ratio.
Reuploud Repository hasyim Juni 2026 Approved by Teddy
Keywords: naringenin; fumaric acid; cocrystal; antioxidant activity; DPPH